The Effect of Mechanical Activation Method on Kaolin-Based Geopolymer Ceramic - Abdul Rahman, Khairun Atiqah; Ahmad, Romisuhani; Wan Ibrahim, Wan Mastura; Abdullah, Mohd Mustafa AlBakri; Abd Rahim, Shayfull Zamree; Mustapa, Nur Bahijah; Shahedan, Noor Fifinatasha (Advanced and Sustainable Technologies (ASET), 2026)
Mechanical activation has emerged as a promising alternative to enhance the reactivity of aluminosilicate materials for geopolymer ceramic production while reducing dependence on energy-intensive thermal activation. This study investigates the effect of mechanical activation on kaolin-based geopolymer ceramics, with particular emphasis on the influence of milling duration on physical, microstructural, and mechanical properties. Kaolin powder was mixed with an alkaline activator consisting of sodium hydroxide and sodium silicate at a mass ratio of (Na2SiO3/NaOH = 0.24), using a solid-to-liquid ratio of 1.0 to form geopolymer paste. The paste was cured at 80°C for 24 hours, followed by crushing into powder form. Mechanical activation was then carried out through ball milling at a constant rotational speed of 100 rpm using different milling durations of 30 minutes, 45 minutes and 60 minutes. The activated powders were then formed and compacted under uniaxial pressing at 5 ton pressure and sintered at 1000°C to obtain geopolymer ceramic bodies. The results revealed that milling duration significantly influenced the properties of the geopolymer ceramics, with an optimum milling time of 45 minutes producing the highest flexural strength and density, as well as the lowest water absorption. SEM analysis confirmed the formation of a dense and homogeneous microstructure at this milling duration. These findings show that mechanical activation is an effective, low-energy approach to improving the performance of kaolin-based geopolymer ceramics.